The effect of academic pressure on learning burnout of college students in the postcovid-19: the mediating effect of academic procrastination - Huang Jing; Chua, Bee Seok (Faculty of Psychology and Education, UMS, 2023)
Learning stress and burnout are common academic problems among college students in recent years. This study aims to investigate the influence of learning stress on the learning burnout of college students in the post-COVID-19 era and the intermediary role of academic procrastination in college students' learning burnout. The study also aims to test differences in learning stress, learning burnout and academic procrastination in demographic variables. This study aims to provide some theoretical guidance for improving the academic situation in China. Academic stress scale, Learning Burnout scale (ULBS) and procrastination rating scale (PASS) were used to investigate 648 college students at the Hunan Institute of Engineering. There were no significant differences in academic stress, academic procrastination and learning burnout in terms of gender and major types (P > 0.05). There was no significant difference in academic procrastination and learning burnout at grade level (P > 0.05). The academic stress score of third-grade students (x ±s = 59.34 ±5.78, P < 0.05) was significantly higher than that of fourthgrade students (x ±s = 56.13 ±4.83, P < 0.05). Correlation analysis shows that there is a significant positive correlation between the three. The results of regression analysis showed that academic stress and academic procrastination had significant effects on learning burnout (R2= 0.417, P < 0.05). The mediating effect test shows that academic procrastination plays an intermediary role in academic stress and learning burnout.